1997
DOI: 10.1021/ja9630710
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Reactions of the Succinimidyl Radical:  A Density Functional Study

Abstract: Recent density functionals and a variety of basis sets were employed in the study of three electronic states of the succinimidyl radical in C 2v symmetry:  2 A 1 (σN), 2 B 1 (πN), and 2 B 2 (σO). The lowest energy σO state is a genuine (local) minimum, as demonstrated by the harmonic vibrational analysis; the stationary points corresponding to the two remaining states are higher-order saddle points on the potential energy surface. Similar results were obtained with the Møller−Plesset method, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
2
2
0
Order By: Relevance
“…Similarly to benzylic bromination, succinimide substitution could be suppressed in NBS-fueled reactions employing acid additives (e.g., p -TsOH) or solvents (lactic acid). This observation may indicate potential involvement of the succinimidyl radical in the formation of 11b – 13b .…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly to benzylic bromination, succinimide substitution could be suppressed in NBS-fueled reactions employing acid additives (e.g., p -TsOH) or solvents (lactic acid). This observation may indicate potential involvement of the succinimidyl radical in the formation of 11b – 13b .…”
Section: Resultssupporting
confidence: 79%
“…Similarly to benzylic bromination, succinimide substitution could be suppressed in NBS-fueled reactions employing acid additives (e.g., p-TsOH) or solvents (lactic acid). This observation may indicate potential involvement of the succinimidyl radical 55 in the formation of 11b−13b. Observation of reaction rates and isolated product yields indicate that the order of reactivity of differently substituted HPBs toward complete cyclization is 1d ≫ 1a ≈ 1b ≫ 1c, reflecting the combined influence of steric and electronic factors.…”
Section: ■ Introductionsupporting
confidence: 80%
“…Initially, Bloomfield proposed that the succinimidyl radical, formed via photolytic cleavage, is the chain carrier for bromination reactions. Later, Goldfinger suggested that the active species in the bromination by NBS is the bromine atom, which also forms via the Bloomfield mechanism. , Several experimental as well as theoretical investigations were taken up subsequently to support both the mechanisms.…”
Section: Bromination Reactionsmentioning
confidence: 99%
“…The σ (O)-radical in the gas phase (solution) is only 0.5 (0.33) kcal/mol lower in energy than the π-radical whereas the σ (N)-centered radical is 2.05 (2.24) kcal/mol higher in energy than the π-radical (Table 1). Using the B3LYP method and different basis sets Gainsforth et al 31 also predicted the O-centered σ-radical to be the most stable whereas an ab initio calculation including electron correlation predicted the π-radical to be more stable than the σ (N)-radical by ca. 5 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%